PENGARUH KOMPETENSI GURU DAN MEDIA GAME KAHOOT DALAM MENINGKATKAN LITERASI DIGITAL AL-QUR’AN HADIS PADA SISWA KELAS 6 MIN KAIMANA - Saeful Ahmad Agus Salim; Hasbullah (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2024)
The objectives of this study are To determine the influence of teacher competencies and kahoot game media on improving the digital literacy of 6th grade students of MIN Kaimana, and.  Determine the effect of the difference in increasing digital literacy between kahoot game media learning and conventional learning. This study uses a type of experimental quantitative research with one group pretest-posttest design. namely by giving pre-test and post test to 46 students as samples. The data analysis in this study was carried out descriptively through the t-test and paired sample t-test. Then the data was processed using SPSS version 25 for windows. The results of the study show that: 1) Teacher competence has an effect on the literacy of 6th grade students of MIN Kaimana.  Kahoot game media has an effect on the digital literacy of 6th grade students of MIN Kaimana. There was a difference in the improvement of students digital literacy before and after being given kahoot game intervention. The evidence is supported by the results of a specific paired sample t-test, obtaining a significant value of p of 0.000.